Unraveling the Link Between Mitochondrial Dynamics and Neuroinflammation - de Oliveira, Lilian Gomes; Angelo, Yan de Souza; Iglesias, Antonio H.; Peron, Jean Pierre Schatzmann (Frontiers in Immunology, 2021)
Neuroinflammatory and neurodegenerative diseases are a major public health problem worldwide, especially with the increase of life-expectancy observed during the last decades. For many of these diseases, we still lack a full understanding of their etiology and pathophysiology. Nonetheless their association with mitochondrial dysfunction highlights this organelle as an important player during CNS homeostasis and disease. Markers of Parkinson (PD) and Alzheimer (AD) diseases are able to induce innate immune pathways induced by alterations in mitochondrial Ca2+ homeostasis leading to neuroinflammation. Additionally, exqacerbated type I IFN responses triggered by by mitochondrial DNA (mtDNA), failures in mitophagy, ER-mitochondriacommunication and mtROS production promote neurodegeneration.On the other hand, regulation of mitochondrial dynamics is essential for CNS health maintenance and leading to the induction of IL-10 and reduction of TNF-α secretion, increased cell viability and diminished cell injury in addition to reduced oxidative stress. Thus, although previously solely seen as as power suppliers to organelles and molecular processes, it is now well established that mitochondria have many other important roles, including during immune responses. Here, we discuss the importance of these mitochondrial dynamics during neuroinflammation, and how they correlate either with the amelioration or worsening of CNS disease.